2017
DOI: 10.1016/j.rmed.2016.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Chronic bronchitis in relation to hospitalization and mortality over three decades

Abstract: Symptoms of chronic bronchitis can help to identify individuals who are at risk for increased hospitalizations and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“… 48 Chronic bronchitis increased all-cause mortality and mortality from respiratory causes, cardiovascular diseases, and cancer. 23 In our study, early onset patients had more frequent exacerbation and poorer health status, which could cause death at younger ages.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“… 48 Chronic bronchitis increased all-cause mortality and mortality from respiratory causes, cardiovascular diseases, and cancer. 23 In our study, early onset patients had more frequent exacerbation and poorer health status, which could cause death at younger ages.…”
Section: Discussionmentioning
confidence: 54%
“… 21 With the progress of disease, chronic bronchitis has an increased risk for frequent exacerbation. 22 , 23 Not only did patients with chronic bronchitis have a higher frequency of exacerbation, but also had longer stays in the hospital. 23 We found that the age of onset is negatively correlated with the number of hospital admissions, which was similar to these results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Tucson Epidemiologic Survey of Airway Obstructive Disease, younger patients with CB had a greater mortality compared to those without CB [28]. In a study of nearly 48,000 men and women, CB was associated with an increased duration of hospitalization and a greater all-cause mortality [25].…”
Section: Discussionmentioning
confidence: 97%
“…The prevalence of CB ranges anywhere from 12.2% in smokers without air ow obstruction to 74% in some COPD cohorts [20][21][22]. CB has been related to an accelerated rate of lung function decline, worse health related quality of life, increased mortality, and an increased risk of respiratory exacerbations in individuals with and without COPD [20,[23][24][25]. In the Copenhagen City Heart Study, chronic mucus hypersecretion was associated with an increased rate of FEV 1 decline over time [24].…”
Section: Discussionmentioning
confidence: 99%